Menggagas Kampung Inggris Padang menjadi Kampung Inggris Masyarakat - Genta Sakti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The aim of this social service is to initiate an English camp in Padang to become an English Camp Village like other famous English camps. This English camp is still in the form of an English course where many students come here to study English for some purposes like to prepare to continue to under graduate degree; to get a job or to pass TOEFL test. As its name suggest, an English camp is not merely Englishmen who live there, but it is only a collection of English courses located in one area. Since there are students coming here to study so that the researcher names this course Kampung Inggris Padang. Based on the initiation carried out for this social service, it was found that there is improvement of students’ ability in speaking English like doing corversation or dialogue and reading aloud English textbook. If it is viewed from the participation of society, there are participations of people around the course like sharing ideas, skill, energy, social participation for better future of Padang English Camp. The prominece is that the realizing and caring of people about their children’s education.